2017
DOI: 10.1016/j.aorn.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Sources of Airborne, Aerosolized, and Contact Contaminants in the OR Environment

Abstract: Surgical site infections are unintended consequences of surgery that can cause harm to patients and place financial burdens on health care organizations. Extrinsic factors in the OR-including health care providers' behavior and practices that modify air movement, the physical environment, equipment, or surgical instruments-can increase microbial contamination. Microbes can be transported into the surgical incision by airborne or contact routes and contribute to a surgical site infection. Simple practices to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Secondarily, it is unknown if the amount of decreased contamination seen in our study will translate to a clinical reduction of SSI; however, it stands to reason that this practice likely would result in decreased contamination that would be considered best practice. 6 Variations in draping procedures at various institutions may limit the generalizability of this technique and findings. However, we chose a manor of draping that has been used at a multitude of institutions in which several of the authors have received training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondarily, it is unknown if the amount of decreased contamination seen in our study will translate to a clinical reduction of SSI; however, it stands to reason that this practice likely would result in decreased contamination that would be considered best practice. 6 Variations in draping procedures at various institutions may limit the generalizability of this technique and findings. However, we chose a manor of draping that has been used at a multitude of institutions in which several of the authors have received training.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Reduction of secondary contamination of the operative field is an important factor in preventing surgical site infections (SSI) that are associated with increased health care cost and morbidity/mortality. [4][5][6][7] Techniques in draping have been developed to successfully combat secondary contamination on the surgeon side. However, recent reports have demonstrated that the far side, opposite the surgeon, is the most prone to secondary contamination from the C-Arm during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne particles can act as transmission vectors for bacteria, thereby increasing the risk of SSI 11 . Armellino 12 and Spencer and Edmiston 13 also concluded that turbulent airflow caused by OR traffic could be linked to an increase in SSIs.…”
Section: Appraising the Literaturementioning
confidence: 99%
“…6,12 Suboptimal cleaning of an operating or procedure room increases the possibility that exogenous source contamination (ie, contaminants from a source other than the patient) may contribute to an SSI. 4,12…”
Section: Operating and Procedures Roomsmentioning
confidence: 99%
“…1 Contaminated surfaces in the OR may contribute to SSIs either through direct contact with the patient or because a health care worker's hands can contact a contaminated surface and then transfer pathogens to other surfaces and to patients. 3 In addition, surgical incisions are susceptible to settling air contaminants from skin squames and microbes from the nasopharynx, such as coagulasenegative staphylococci, 4 one of the organisms most commonly found in cultures from SSI wounds. 5 Effective and correctly performed environmental cleaning and disinfection can decrease microbial contamination of surfaces in the OR and help prevent SSIs.…”
mentioning
confidence: 99%